1988
DOI: 10.1099/00221287-134-11-2867
|View full text |Cite
|
Sign up to set email alerts
|

Serological Properties and Immunobiological Activities of Lipopolysaccharides from Black-pigmented and Related Oral Bacteroides Species

Abstract: Lipopolysaccharides (LPS) from five species of oral Bacteroides, B. gingivalis strains 38 1 and ATCC 33277, B. oralis ATCC 33269, B. 1oescheiiATCC 15930, B. intermedius ATCC 2561 1 and B. corporis ATCC 33547, were extracted from whole cells by the phenol/water procedure, and subsequently purified by treatment with nuclease and ultracentrifugation. The LPS were composed of hexoses, glucosamine, fatty acids and phosphorus. Heptose and 2-keto-3-deoxyoctonate were not detected. The LPS preparations from B. gingiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…gingiuulis 381 promotes macrophage secretion of interleukin-1 in lipopolysaccharide-responder macrophages (isolated from lipopolysaccharide-responder C3H/HeN mice). The secretory response from lipopolysaccharide-responder macrophages was seven-fold higher than that observed for low-responder macrophages isolated from C3H/HeJ mice (54). Consistent with most reports described above, interleukin-1 synthesis induced by l?…”
Section: Chemically Defined Lipid a Of I? Gingivalis Is Reportedsupporting
confidence: 90%
See 1 more Smart Citation
“…gingiuulis 381 promotes macrophage secretion of interleukin-1 in lipopolysaccharide-responder macrophages (isolated from lipopolysaccharide-responder C3H/HeN mice). The secretory response from lipopolysaccharide-responder macrophages was seven-fold higher than that observed for low-responder macrophages isolated from C3H/HeJ mice (54). Consistent with most reports described above, interleukin-1 synthesis induced by l?…”
Section: Chemically Defined Lipid a Of I? Gingivalis Is Reportedsupporting
confidence: 90%
“…Consistent with most reports described above, interleukin-1 synthesis induced by l? gingiuulis lipopolysaccharide in C3H/HeN macrophages was four times lower than that produced with an equivalent level of E. coli lipopolysaccharide (54). Bramanti et al examined the effect of lipopolysaccharide isolates from selected strains of l?…”
Section: Chemically Defined Lipid a Of I? Gingivalis Is Reportedmentioning
confidence: 99%
“…The production of (1), ®broblasts (2), macrophages (8), bone marrow cells (26) and human whole blood (27) is stimulated by A. actinomycetemcomitans LPS. P. gingivalis LPS also induces IL-1 release from macrophages (4,7,28,29) and ®broblasts (30). Some of these results indicated that the levels of IL-1 induced by A. actinomycetemcomitans and E. coli LPS are higher than those induced by P. gingivalis LPS in vitro (1,2,4,5).…”
Section: Discussionmentioning
confidence: 97%
“…Early studies demonstrated that LPS from P. gingivalis strains induced marked mitogenic responses and polyclonal B-cell activation in spleen cells, activated both neutrophils and macrophages, and enhanced IL-1 production by murine peritoneal macrophages (Fujiwara et al ., 1988;Isogai et al ., 1988). However, Kesavalu et al .…”
Section: (V) Animal Modelsmentioning
confidence: 99%